2019
DOI: 10.1111/ppl.13024
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione and hydrogen sulfide are required for sulfur‐mediated mitigation of Cr(VI) toxicity in tomato, pea and brinjal seedlings

Abstract: In plants, investigation on heavy metal toxicity and its mitigation by nutrient elements have gained much attention. However, mechanism(s) associated with nutrients‐mediated mitigation of metal toxicity remain elusive. In this study, we have investigated the role and interrelation of glutathione (GSH) and hydrogen sulfide (H2S) in the regulation of hexavalent chromium [Cr(VI)] toxicity in tomato (Solanum lycopersicum), pea (Pisum sativum) and brinjal (Solanum melongena) seedlings, supplemented with additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Although in animals, the role of 2‐OG as a regulator of the oxidative stress is known (Graf et al 2013, Zdzisińska et al 2017), the implication of 2‐OG priming in mitigating metal toxicity in plants was not known. Moreover, although NO is now a well‐known signaling molecule involved in regulating stress responses in plants (Xiong et al 2010, Sahay and Gupta 2017, Nabi et al 2019, Terrón‐Camero et al 2019, Kushwaha and Singh 2020, Piacentini et al 2020, Sharma et al 2020), its involvement in 2‐OG priming‐mediated mitigation of metal toxicity was unidentified so far. Therefore, the results of this study are promising from a metal toxicity mitigation point of view as 2‐OG‐priming is capable of significantly attenuating As V toxicity in tomato roots by involving the endogenous NO level.…”
Section: Discussionmentioning
confidence: 99%
“…Although in animals, the role of 2‐OG as a regulator of the oxidative stress is known (Graf et al 2013, Zdzisińska et al 2017), the implication of 2‐OG priming in mitigating metal toxicity in plants was not known. Moreover, although NO is now a well‐known signaling molecule involved in regulating stress responses in plants (Xiong et al 2010, Sahay and Gupta 2017, Nabi et al 2019, Terrón‐Camero et al 2019, Kushwaha and Singh 2020, Piacentini et al 2020, Sharma et al 2020), its involvement in 2‐OG priming‐mediated mitigation of metal toxicity was unidentified so far. Therefore, the results of this study are promising from a metal toxicity mitigation point of view as 2‐OG‐priming is capable of significantly attenuating As V toxicity in tomato roots by involving the endogenous NO level.…”
Section: Discussionmentioning
confidence: 99%
“…Paul and Roychoudhury (2019), Pandey and Gautam (2019) Research articles have covered diverse new roles of H 2 S and NO in regulating abiotic stress in plants. Kushwaha and Singh (2019) and Ahmad et al (2019) have reported various mechanisms through which H 2 S regulates chromium toxicity in crop plants. Regulatory roles of NO and H 2 S were reported for salt and drought stress, as well as iron deficiency in plants (Batista et al 2019, Gohari et al 2019, Jahan et al 2019, Kaya et al 2019a).…”
mentioning
confidence: 99%
“…This interplay between glutathione and hydrogen sulfide points to a universal importance for the regulation of plant tolerance to heavy metal stress. This notion was proved by Kushwaha and Singh [158] who showed that in S. lycopersicum, Pisum sativum, and Solanum melongena seedlings that the interplay between glutathione and hydrogen sulfide regulates the mitigation of chromium toxicity. Even though studies have highlighted a link between glutathione and hydrogen sulfide in plants under heavy metal stress, these studies only focused on applying exogenous hydrogen sulfide.…”
Section: Amplification Of the Ros Signal By Glutathione Could Improvementioning
confidence: 92%